Heat shrink film for paper ream packaging
By optimizing the ratio of PE base resin and adding organic montmorillonite and other components, the cutability, transparency and shrinkage uniformity of the heat shrink film for paper packaging is improved, and the shortcomings in the prior art are solved, and the safety and environmental protection needs of high-end paper packaging are met.
Patent Information
- Application Number
- CN202510736203.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-04
- Publication Date
- 2025-07-29
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing paper makes the heat shrink film for paper packaging inadequate cutting, low transparency, poor antistatic properties, uneven shrinkage, insufficient flame retardancy and unenvironmental protection, and cannot meet the needs of high-end paper packaging.
Using a combination of PE base resin, organic montmorillonite, antistatic agent, flame retardant, compatible agent, plasticizer, light calcium carbonate, lubricant and antioxidant with specific ratios, the easy cutability and transparency are improved through molecular chain flexibility adjustment and nanolayer interlayer structure, and the compatibility and antistatic effect are improved through complex compositions. The crystal structure is added to refine the crystal structure to improve shrinkage uniformity and flame retardancy.
It improves the ease of cutting, transparency and shrinkage uniformity of the heat-shrinking film, reduces the risk of burrs during cutting, ensures that the membrane body is tightly fits into the paper, meets flame retardant and environmental protection requirements, and improves packaging safety and display effect.
Smart Images

Figure BDA0005433370640000051 
Figure BDA0005433370640000061 
Figure BDA0005433370640000062
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of packaging materials, and particularly relates to a heat shrinkable film for wrapping paper reams. Background Art
[0002] As a common form of unit packaging for paper, paper reams need to have good protection and usability. Traditional paper ream packaging mostly uses ordinary polyethylene (PE) heat shrinkable films. However, the existing heat shrinkable films have the following technical bottlenecks:
[0003] ① Insufficient cuttability: When cutting traditional PE-based heat shrinkable films, phenomena such as rough edges, film body tearing, uneven cut surfaces, and cut surface adhesion are likely to occur, resulting in low packaging efficiency, increased processing costs, and possible scratching of operators.
[0004] ② Transparency defects: Ordinary PE films have high crystallinity and low transparency, making it difficult to directly identify information such as the specifications and batches of the paper inside the packaging, affecting the packaging display effect and increasing warehousing management costs.
[0005] ③ Insufficient antistatic performance: Paper is prone to generating static electricity during friction, which can adsorb dust or pose a fire risk, restricting its application in high-end paper packaging scenarios.
[0006] ④ Insufficient shrinkage rate: The shrinkage uniformity is poor, resulting in a poor fitting effect.
[0007] ⑤ Insufficient flame retardancy: Ordinary PE films are flammable, posing a safety hazard and not meeting the safety requirements for paper warehousing.
[0008] ⑥ Insufficient environmental friendliness: Containing halogenated flame retardants or non-degradable components, it does not conform to the trend of green packaging.
[0009] In the prior art, improving the cuttability is often achieved by adding talcum powder or plasticizers, but this will sacrifice transparency; while the compounding of flame retardants and antistatic agents is prone to poor compatibility and cannot meet the requirements of high efficiency, safety, and aesthetics for paper ream packaging. Summary of the Invention
[0010] The purpose of the present invention is to provide a heat shrinkable film for wrapping paper reams, which has the characteristics of easy cutting and high transparency.
[0011] The purpose of the present invention can be achieved by the following technical solutions:
[0012] A heat shrinkable film for wrapping paper reams, comprising the following components and parts by weight:
[0013] 90 - 110 parts of PE base resin, 3 - 5 parts of organic montmorillonite, 3 - 5 parts of antistatic agent, 2 - 6 parts of flame retardant, 3 - 5 parts of compatibilizer, 0.5 - 1.6 parts of plasticizer, 0.2 - 1.3 parts of light calcium carbonate, 0.1 - 0.5 parts of lubricant, 0.1 - 0.3 parts of antioxidant.
[0014] As a preferred technical solution of the present invention, the PE base resin comprises 50 - 60 wt% LDPE, 20 - 40 wt% LLDPE, 5 - 15 wt% EMA, and 3% - 10 wt% metallocene polyethylene.
[0015] In this way, EMA (ethylene - methyl acrylate copolymer) and metallocene polyethylene (mPE) introduce polar groups into the PE base resin by adjusting the molecular chain flexibility, can combine with the nano - interlayer structure of organic montmorillonite, enhance the intermolecular force, refine the cell structure, reduce the irregular tearing during cutting, and thus further promote the easy - cutting property of the heat - shrinkable film. Moreover, these several polymers are co - blended low - crystalline or amorphous polymers, which can reduce the crystallinity of the PE base resin and improve the transparency.
[0016] Among them, LDPE is low - density polyethylene to provide flexibility and shrinkability; LLDPE is linear low - density polyethylene to enhance the tensile strength. EMA improves the compatibility and easy - cutting property, reduces the stress concentration during cutting, mPE enhances the film toughness and cutting smoothness, and enhances the heat - shrinkage performance and mechanical strength.
[0017] Specifically, the organic montmorillonite is an organically modified montmorillonite, which ensures the compatibility with the PE base resin; and synergistically acts with EMA and metallocene polyethylene to improve the interfacial bonding force of the film body through intercalation compounding, and further enhances the easy - cutting property. In the present invention, organic montmorillonite is added, and the organic montmorillonite is uniformly dispersed in the matrix to form stress concentration points, inducing fracture along the interface of the organic montmorillonite particles during cutting, thereby improving the easy - cutting property of the heat - shrinkable film.
[0018] Furthermore, the organic montmorillonite is modified with cetyltrimethylammonium bromide. The layer spacing of the organic montmorillonite is ≥ 3 nm.
[0019] As a preferred technical solution of the present invention, the antistatic agent is glycerol monostearate (GMS) or a compound of GMS and polyether - type antistatic agent. In this way, this specific type of antistatic agent forms a conductive layer through surface migration to improve the antistatic effect.
[0020] As a preferred technical solution of the present invention, the flame retardant is at least one of aluminum hydroxide, magnesium hydroxide, a compound of aluminum hydroxide and phosphorus - nitrogen - based intumescent flame retardant (IFR), and tribromoneopentyl phosphate.
[0021] As a preferred technical solution of the present invention, the compatibilizer is maleic anhydride grafted polyethylene (PE-g-MAH) to enhance the interfacial compatibility between the inorganic filler and the organic resin. Among them, the IFR flame retardant and the GMS antistatic agent are uniformly dispersed through the compatibilizer to improve the compatibility.
[0022] As a preferred technical solution of the present invention, the plasticizer is dioctyl adipate. Adding a specific plasticizer in the present invention can reduce the glass transition temperature, reduce the intermolecular force, and improve the cutability of the heat shrinkable film.
[0023] As a preferred technical solution of the present invention, the particle size of the light calcium carbonate is 80-150 nm. Among them, the light calcium carbonate can form tiny protrusions on the film surface, reduce the contact area, reduce the adsorption force between the films, and improve the cutability of the shrink film.
[0024] As a preferred technical solution of the present invention, the lubricant is at least one of calcium stearate, paraffin wax, and polyethylene wax. Adding a lubricant can appropriately reduce the surface energy of the heat shrinkable film, reduce the adhesion when the film is cut, and promote the cutability of the heat shrinkable film.
[0025] As a preferred technical solution of the present invention, the antioxidant is at least one of antioxidant 1010 and antioxidant 168.
[0026] Among them, antioxidant 1010, namely: pentaerythritol tetra[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]; antioxidant 168, namely: tris[2,4-di-tert-butylphenyl] phosphite. By adding an antioxidant, thermal oxidative degradation can be inhibited and the service life can be extended.
[0027] As a preferred technical solution of the present invention, it further includes 0.05-0.25 parts of a crystal nucleating agent. In this way, the crystal nucleating agent increases the number of crystal nuclei, refines the crystal particles, promotes the resin to form a uniform fine crystal structure, reduces light scattering, and improves transparency.
[0028] Further preferably, the crystal nucleating agent is preferably a sorbitol-based transparent nucleating agent or a sodium benzoate-based nucleating agent.
[0029] A method for preparing the heat shrinkable film as described above includes the following steps:
[0030] S1. Premix LDPE, LLDPE, EMA and metallocene polyethylene, and melt-extrude and pelletize at 180-200 °C to obtain a PE base resin;
[0031] S2. Premix the PE base resin prepared in step S1 with other components, add them to an extruder for blending, then heat to 180-220 °C for melt extrusion, then biaxially stretch, cool and shape, and slit and wind up to obtain a heat shrinkable film.
[0032] Preferably, in step S2, the PE base resin and other components are premixed in a high-speed mixer at a temperature of 60-80°C for 10-20 minutes to form a uniform premix.
[0033] Preferably, in step S2, the longitudinal and transverse draw ratios of the biaxial stretching are 1.5-2.5:1.
[0034] Specifically, in step S2, the longitudinal and transverse draw ratios of the biaxial stretching are 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2.0:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1 or 2.5:1.
[0035] Preferably, in step S2, during the cooling and shaping, it is cooled to room temperature by an air ring.
[0036] Preferably, the thickness of the heat-shrinkable film is 55-80 μm.
[0037] Furthermore, the thickness of the heat-shrinkable film is 60-75 μm.
[0038] Advantages of the present invention:
[0039] By optimizing the formulation of the PE base resin and adding components such as a grain nucleating agent and organic montmorillonite, the shrinkage rate, transparency, and cutability of the heat-shrinkable film are improved in the present invention, reducing the risk of burrs or damage during cutting, meeting the requirements of industrial production, ensuring that the film body closely adheres to the paper, preventing loosening during transportation or storage, while meeting the requirements of flame retardancy and environmental protection and enhancing packaging safety. Therefore, the heat-shrinkable film of the present invention is applicable to the field of paper ream packaging and has broad market prospects. Detailed implementation manners
[0040] To further elaborate on the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following, in combination with embodiments, details the specific implementation manners, structures, features, and their effects of the present invention as follows.
[0041] Embodiment 1
[0042] A heat-shrinkable film for paper ream packaging comprises the following components and parts by weight:
[0043]
[0044] The specific preparation process is as follows:
[0045] S1: After premixing LDPE, LLDPE, EMA, and metallocene polyethylene, it is melt-extruded and pelletized at 190±2°C to obtain a PE base resin;
[0046] S2: Premix the PE base resin obtained in step S1 and other components in a high-speed mixer at 70 °C for 15 minutes to form a uniform premix, and then add it to a twin-screw extruder for blending. The screw speed is 180 rpm. Subsequently, heat it to 210 ± 2 °C for melting, then enter the blown film die head to extrude a film bubble, and draw the film bubble to a stretching oven for biaxial stretching at a longitudinal and transverse stretching ratio of 2:1 to make the film thickness 65 ± 5 μm. Finally, cool it to room temperature for shaping through an air ring, slit and wind up to obtain a heat-shrinkable film.
[0047] Example 2
[0048] A heat-shrinkable film for paper ream wrapping, comprising the following components and parts by weight:
[0049]
[0050] Its preparation process is the same as that of Example 1.
[0051] Example 3
[0052] A heat-shrinkable film for paper ream wrapping, comprising the following components and parts by weight:
[0053]
[0054]
[0055] Its preparation process is the same as that of Example 1.
[0056] Comparative Example 1
[0057] Compared with Example 1, the difference in Comparative Example 1 is that in Comparative Example 1, the organic montmorillonite is replaced with nano kaolin modified by a silane coupling agent, and the other components, preparation steps and parameters are the same.
[0058] Comparative Example 2
[0059] Compared with Example 1, the difference in Comparative Example 2 is that in Comparative Example 2, the light calcium carbonate is replaced with heavy calcium carbonate, and the lubricant is adjusted to 0.5 part, and the other components, preparation steps and parameters are the same.
[0060] Comparative Example 3
[0061] Compared with Example 2, the difference in Comparative Example 3 is that in Comparative Example 3, EMA is missing, and the other components, preparation steps and parameters are the same.
[0062] Comparative Example 4
[0063] Compared with Example 3, the difference in Comparative Example 4 is that in Comparative Example 4, metallocene polyethylene is missing, and the other components, preparation steps and parameters are the same.
[0064] Comparative Example 5
[0065] Compared with Example 1, the difference in Comparative Example 5 is that the grain nucleating agent is missing in Comparative Example 5, and the other components, preparation steps and parameters are the same.
[0066] The heat shrinkable films prepared in Examples 1-3 and Comparative Examples 1-5 were numbered. Among them, the heat shrinkable films of Examples 1-3 were numbered 1-3, and the heat shrinkable films of Comparative Examples 1-5 were numbered 4-8. Subsequently, the following performance tests were carried out respectively:
[0067] (1) Shrinkage performance test
[0068] Using an FST-3102 film heat shrinkage performance tester, in accordance with the national standard GB / T 34848-2017 "Test Method for Shrinkage Performance of Heat Shrinkable Films", the heat shrinkable film was cut into specimens of 100 mm × 100 mm and placed in a heating chamber at 120 °C for 20 seconds, and its shrinkage rate (%) was recorded.
[0069] (2) Ease of cutting test
[0070] Using an intelligent electronic tensile testing machine, a customized cutting blade (edge angle 30°) was installed, and the heat shrinkable films of the examples and comparative examples (size 100 mm × 100 mm) were vertically cut at a speed of 50 mm / min. The initial cutting force (N), the average force during cutting (N) and the burr rate of the cutting edge were recorded.
[0071] Among them, the smaller the cutting force, the smoother the edge. When the burr rate of the cutting edge ≤ 5%, it is recorded as no burr; when 5% < the burr rate of the cutting edge ≤ 30%, it is recorded as a small amount of burrs; when the burr rate of the cutting edge > 30%, it is recorded as obvious burrs.
[0072] (3) Transparency test
[0073] Using a WGT-S haze and light transmittance measuring instrument, in accordance with the national standard GB 2410-2008 "Test Method for Transmittance and Haze of Transparent Plastics", the light transmittance (%) of the heat shrinkable film at a wavelength of 550 nm was measured.
[0074] (4) Antistatic performance test
[0075] Using a WG-268 surface resistivity tester, in accordance with the national standard GB 1410-2006 "Test Method for Volume Resistivity and Surface Resistivity of Solid Insulating Materials", the surface resistivity (Ω) of the surface of the heat shrinkable film was measured.
[0076] The test results are shown in Table 1.
[0077] Table 1
[0078]
[0079] As can be seen from the test results in Table 1, the heat-shrinkable films of Examples 1-3 have excellent effects in terms of shrinkage uniformity, easy cutability, light transmittance, and antistatic performance, indicating that by optimizing the ratio of the PE base resin and adding components such as crystal nucleating agents and organic montmorillonite, the present invention significantly improves the shrinkage rate, transparency, and easy cutability of the heat-shrinkable film. The test data show that its comprehensive performance has significant advantages compared with the comparative example, meeting the high-quality requirements of paper ream packaging.
[0080] The above are only the preferred embodiments of the present invention and do not impose any formal limitations on the present invention. Although the present invention has been disclosed above with preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or equivalent variations by using the disclosed technical content within the scope of the technical solution of the present invention. However, any brief modifications, equivalent variations, and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A heat shrinkable film for wrapping paper reams, characterized in that, It comprises the following components by weight parts: 90 - 110 parts of PE base resin, 3 - 5 parts of organic montmorillonite, 3 - 5 parts of antistatic agent, 2 - 6 parts of flame retardant, 3 - 5 parts of compatibilizer, 0.5 - 1.6 parts of plasticizer, 0.2 - 1.3 parts of light calcium carbonate, 0.1 - 0.5 parts of lubricant, and 0.1 - 0.3 parts of antioxidant.
2. The heat shrinkable film according to claim 1, wherein The PE base resin contains 50 - 60wt% LDPE, 20 - 40wt% LLDPE, 5 - 15wt% EMA, and 3% - 10wt% metallocene polyethylene.
3. The heat shrinkable film according to claim 1, wherein The organic montmorillonite is modified with cetyltrimethylammonium bromide; the layer spacing of the organic montmorillonite is ≥3nm.
4. The heat shrinkable film according to claim 1, characterized in that, The antistatic agent is glycerol monostearate (GMS) or a compound of GMS and polyether antistatic agent.
5. The heat shrinkable film according to claim 1, characterized in that, The flame retardant is at least one of aluminum hydroxide, magnesium hydroxide, a compound of aluminum hydroxide and phosphorus - nitrogen intumescent flame retardant (IFR), and tribromoneopentyl phosphate; the lubricant is at least one of calcium stearate, paraffin wax, and polyethylene wax; the antioxidant is at least one of antioxidant 1010 and antioxidant 168.
6. The heat-shrinkable film according to claim 1, wherein The compatibilizer is maleic anhydride grafted polyethylene; the plasticizer is dioctyl adipate.
7. The heat-shrinkable film according to claim 1, wherein The particle size of the light calcium carbonate is 80 - 150nm.
8. The heat-shrinkable film according to claim 1, wherein It also includes 0.05 - 0.25 parts of crystal nucleating agent.
9. A method for preparing a heat-shrinkable film according to any one of claims 1 to 8, characterized in that, The preparation method includes the following steps: S1. Premix LDPE, LLDPE, EMA, and metallocene polyethylene, and then melt - extrude and pelletize at 180 - 200°C to obtain PE base resin. S2. Premix the PE base resin obtained in step S1 with other components, then add them into an extruder for blending. Subsequently, heat to 180 - 220°C for melt - extrusion, then perform biaxial stretching, cooling and shaping, and slitting and winding to obtain a heat - shrinkable film.
10. The preparation method according to claim 9, characterized in that, In step S2, the PE base resin and other components are premixed in a high - speed mixer at a temperature of 60 - 80°C for 10 - 20 minutes to form a uniform premix; the longitudinal and transverse stretching ratios of the biaxial stretching are 1.5 - 2.5:1; the thickness of the heat - shrinkable film is 55 - 80μm.